Reconstruction of the network of experimentally validated AMP-drug combinations against Pseudomonas aeruginosa infections - Jorge, Paula (2016)
The combination of antimicrobial products is a promising biomedical strategy against the ever growing number of resistant strains emerging in healthcare and community settings. Agents with alternative modes of action, such as antimicrobial peptides (AMPs), and the efficacy of combined actions are being evaluated. Despite the availability of various antimicrobial data repositories, a wealth of information remains scattered through the scientific literature. This work introduces the automated curation pipeline implemented to produce the first ever network reconstruction of AMP-drug combinations. This network relates to antimicrobial combinations experimentally tested against Pseudomonas aeruginosa infections and includes 239 combinations among AMPs and other antimicrobials. The aim is to provide a global view of available interaction data and help design new antimicrobial studies. Reconstruction is on-going, coping with new experimental results for P. aeruginosa, and will be soon extended to other meaningful microbial pathogens. The network is publicly accessible at http://sing.ei.uvigo.es/antimicrobialCombination/.